Salivary Oxidant/Antioxidant Status in Chronic Temporomandibular Disorders Is Dependent on Source and Intensity of Pain – A Pilot Study - Vrbanović, Ema; Alajbeg, Iva Z.; Vuletić, Lea; Lapić, Ivana; Rogić, Dunja; Andabak Rogulj, Ana; Illeš, Davor; Knezović Zlatarić, Dubravka; Badel, Tomislav; Alajbeg, Ivan (Frontiers in Physiology, 2018)
Temporomandibular disorders (TMD) have been associated with altered salivary oxidative status, but the relation with pain source and pain severity isn't clarified. With the aim to assess their interaction with TMD, we compared levels of selected salivary oxidative stress (OS) markers (glutathione peroxidase, superoxide dismutase, total antioxidant capacity (TAC), uric acid, 8-hydroxydeoxyguanosine, malondialdehyde) and salivary cortisol (SC) as a stress indicator, between 20 TMD patients and 15 healthy control subjects. In order to record differences relating to pain source and severity, patients were respectively classified according to specific diagnoses (myofascial pain or disc displacement (DD)), and pain intensity (high or low). TAC was significantly higher in TMD patients than in controls (morning p=0.015; afternoon p=0.005). Significant differences were also observed when TAC levels between high-intensity pain patients and controls were compared, as well as between DD patients and controls. In logistic regression analysis, higher levels of TAC were related to DD (morning OR:1.66, 95%CI:1.05–2.64, p=0.029; afternoon OR:2.10, 95%CI:1.11–3.98, p=0.021), and to high-intensity pain (morning OR:1.81, 95%CI:1.04–3.15, p=0.037; afternoon OR:1.79, 95%CI:1.02–3.14, p=0.043). We also found that morning SC was positively correlated with antioxidant parameters in TMD patients. Our data suggest compensatory mechanism as response to higher level of stress. This stress could be extrinsic and lead towards TMD, or intrinsic, emerging from established TMD, or could be both. The intensity and the source of pain should be considered important factors in future investigations evaluating salivary OS markers in TMD patients.